SOSIALISASI PENERAPAN JAGA JARAK DAN PEMAKAIAN MASKER PADA PEDAGANG DAGING BABI DI PASAR KASIH NAIKOTEN, KOTA KUPANG, NUSA TENGGARA TIMUR - Yeremia Yobelanno Sitompul; Diana Agustiani Wuri; Larry R. W. Toha; Nancy D. F. K. Foeh (Universitas Nusa Cendana, 2021)
The prevention of COVID-19 widespread needs to be understood by the community, especially people who unfortunately have to work face to face with buyers, such as meat traders in local markets. It is important to ensure them understanding the prevention of COVID-19 so they can keep having income with a minimum chance of being infected by COVID-19. The purpose of this community service is to increase the awareness of pork trader group participation in Kasih Market, Naikoten, Kupang City, East Nusa Tenggara Province in preventing the COVID-19 widespread by doing physical distancing and wearing masks. The method of implementing this community service is the distribution of questionnaires (pretest and posttest form) and socialization. The pre-socialization questionnaire was given to know pork traders’ knowledge about physical distancing and mask usage. The socialization was delivered by explaining how to do correct physical distancing and mask usage. The post-socialization questionnaire was given as the indicator of the success of the community service. The questionnaire results showed a significant increase in pork traders’ understanding of physical distancing, from around 67% to 92%, and the understanding of masks usage, from around 42% to 92%. Therefore, it is hoped that the pork traders can apply the knowledge correctly and participate in preventing the spread of COVID-19 in the market.